COMPARISON OF THE TAX NEUTRALITY BY MEANS OF THE EFFECTIVE TAX RATES IN THE CZECH REPUBLIC IN THE YEARS 2000 - 2010 - Holeckova, Jaroslava (European Scientific Journal, ESJ, 2013)
The objective of this paper is to examine tax neutrality; that is, to a tax that leaves corporate decisions as to investments or sources of financing unchanged. The tax system that seeks to raise revenue in ways that avoid distortion effects is considered neutral tax system. This point is of great importance, for it defines one aim of the current tax system and one criterion by which it may be assessed The use of effective tax rates on different types of capital assets and sources of financing and to assess on the base of calculation of the tax wedges the degree to which taxation affects the incentive to undertake investment in the Czech Republic. The precise methodology used to calculate effective tax rates on marginal investments is based on an approach developed by the King and Fullerton methodology (1984), which has become the most widely accepted method adopted to calculating effective tax rates (tax wedges). The tax wedge will vary according to the type of asset: machinery, buildings, inventory (because of different capital allowance rates relative to the assumed true economic depreciation rates) and the type of finance sources: new equity, debt, retained earnings (because the tax treatment of debt, dividends and retained earnings differs). Effective tax rates take into account not only the statutory corporate tax rate, but also other aspects of the tax system which determine the amount of tax paid and profitability of investment, a consideration of personal taxes.